Effects of Strike Participation on the Political Consciousness of Canadian Postal Workers - Langford, Tom (Relations industrielles / Industrial Relations, 1996)
Marxists have long argued that major strikes produce an explosion of workers' class consciousness. This article discusses some weaknesses of the explosion-of-consciousness thesis, and tests research hypotheses using data from a case study of the 1987 strike by the Hamilton local of the Canadian Union of Postal Workers. A major finding is that an increase in a postal worker's negative attitudes toward out-groups did not necessarily go hand in hand with an increase in that striker's positive identifications with in-groups such as fellow workers, the local union and the labour movement. This supports treating the in-group and out-group dimensions of class consciousness as distinct. A second finding supports the hypothesis that an explosion of in-group consciousness due to inter-group conflict is more likely to occur among workers who are already identified with the in-group.